Mesotherapy – a method of facial skin rejuvenation from an interdisciplinary perspective on improving facial aesthetics - Matthews-Brzozowska, Teresa; Łącka, Monika; Bernacka, Magdalena; Lichaj, Maciej (Journal of Medical Science, 2017)
Mesotherapy has been used in medicine since the 1950s and for aesthetic procedures since the 1970s. In the medical literature there are numerous reports about the positive effect of mesotherapy with regard to rejuvenating and improving the appearance of facial skin (reduction of fine wrinkles and discolouration, facial contour correction, improvement in skin tightness and elasticity). The variety of formulations used and the different techniques for administering them mean that the subjectively observed effects of mesotherapy cannot be objectively verified. To date, only a few studies have been published in the international literature where histopathological, ultrasound, and electron microscopy examinations were performed to confirm the efficacy of this method. Most studies, however, have been based on assessing subjective improvement. The aim of this paper was to review literature on the subject, namely 15 full-text reports on the effects of mesotherapy in the treatment of facial skin. The findings of the review show that the studies published to date are based primarily on subjective assessment methods, presenting the results of mesotherapy procedures through an analysis of "before and after" medical photographic documentation. It would seem necessary that further research should be conducted based on a unified protocol.
Keywords: mesotherapy; revitalisation/rejuvenation; aesthetic medicine; face